Strategy of Tourist Events Museum De Javasche Bank Surabaya - Citra Anggraini Tresyanto; Deograsias Joseph (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Surabaya is one of the cities in Indonesia which has quite a lot of museum rows with various types of museums. One type of scientific museum is the De Javasche Bank Museum. The collection of historical objects and the historical value of the building is very interesting in fact unable to attract visitors to come and learn. De Javasche Bank Museum is also one of the museums in Surabaya whose existence is not widely known by the public. It is necessary for an integrated marketing communication strategy to solve this problem. One of the integrated marketing communication tools from Sales Promotion is Event Marketing. This research uses qualitative research methods with a descriptive analysis approach. Data collection techniques in this research are field studies and literature studies. Primary data in this study is data that is directly obtained from museum managers, visitors, and the community through observations and interviews, while secondary data comes from literature.